Common behaviors related to corruption in Lima university students - Freundt-Thurne, Úrsula (2020)
Corruption is one of the main problems in Peru, along with crime and citizen insecurity, violence against women, drug use, poverty and unemployment. The latter has increased in recent months due to the COVID-19 pandemic. The objective of the study was to determine common behaviors associated with corruption among university students from Lima, Peru. Among the common behaviors identified, it was found that students, at least once, had bought pirated products (94.4%), offered false excuses to their parents to justify where they were (88.5%), and cheated on exams (74.4%). These behaviors were observed in both men and women. The results show that these behaviors are the result of a broader educational problem that has permeated the morals and ethics of society.